The Fallacy of Full Compensation - Jeffrey Standen (Washington University Law Quarterly, 1995)
Parts II and III discuss the practical problem with prohibitory remedies, that they are in fact inadequate to the tasks the critics have posited for them. Parts IV and V present the normative justification for a remedial system that relegates prohibitory remedies, and thus full compensation, to a secondary role.
Keywords: Equitable remedies (Law); Compensatory damages